The impact of corporate social responsibility on firm reputation and organizational citizenship behavior: The mediation of organic organizational cultures - Ali, Hussain; Yin, Jianhua; Manzoor, Faiza; An, Mengmeng (Frontiers in Psychology, 2023)
This study inspects the impact of corporate social responsibility on firm reputation and organizational citizenship behavior, along with the mediating inclusion of organic organizational cultures (Clan & Adhocracy) in the medium and large enterprises of Pakistan. Smart PLS was highly concerned with determining the nexus and investigating the supposed hypotheses. For data collection, the convenience sampling technique was used. The results displayed that CSR has a significant and optimistic effect on a firm reputation and employees' OCB. Secondly, the outcomes showed a positive and full mediation effect of organic organizational cultures between CSR and firm reputation but a partial mediation effect of organic organizational cultures between CSR and employees OCB. Further, the results demonstrated a positive and significant influence of employees' OCB on a firm reputation. The extensive analysis of all factors of the study was autonomously examined to identify the insights that verify how the inclusion of organic organizational cultures can boost the firm reputation and employees' OCB. Theoretical implications and future research direction are discussed.